(untitled) (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
The idea behind this study emerged from an attempt to explore the cumulative creative values within jurisprudential texts. Specifically, focused on a sample drawn from the Maliki jurisprudential writings in Libyan history. The aim was to leverage contemporary cognitive achievements and employ modern theories and studies related to communication and influence. Additionally, we examined the active role of the recipient in empowering the jurisprudential text, emphasizing complete and unimpaired communicative elements. This research sample was deliberately chosen within the conference’s thematic framework. It represents a facet of literary heritage from the 10th Hijri century, shedding light on its creative contributions to serving jurisprudential discourse. By invoking critical and artistic components, we sought to establish a methodological foundation for shaping the linguistic architecture of jurisprudential texts. The central question driving our inquiry revolves around the effectiveness of reception in the context of Sheikh Abdul Salam Al-Asmar. As he engages with jurisprudential texts, how does the critical value of reception manifest in constructing the linguistic structure of his jurisprudential letters? These letters, received by diverse recipients across various spatial and temporal contexts, prompt us to explore the nuanced and multifaceted stylistic patterns in directing textual movement and producing foundational jurisprudential content based on preceding texts by Sheikh Abdul Salam Al-Asmar.